Case Report: Acute common peroneal nerve injury after posterior lumbar decompression surgery - Wang, Peng Wei; Chung, Ming Hsuan; Hueng, Dueng Yuan; Hsia, Chung Ching (Frontiers in Surgery, 2024)
Spine surgery is a prevalently performed procedure. Some authors have proposed an age-related surge in surgical and general complications. During spine surgery, patients are placed in positions that are not physiologic, would not be tolerated for prolonged periods by the patient in the awake state, and may lead to complications. Understanding these uncommon complications and their etiology is pivotal to prevention and necessary. The patient is a 76-year-old woman referred to the outpatient department of neurosurgery in February 2022 by her physiatrist with a chief complaint of chronic low back pain and numbness over the left leg. Lumbar spine magnetic resonance imaging revealed degenerative disc disease and posterior disc bulging at the levels of L2/3∼L5/S1 with compression of the thecal sac. After receiving anti-inflammatory medication, nerve block and caudal block, her symptoms persisted. She was referred to a neurosurgeon for surgical intervention. We diagnosed spinal stenosis with left L3 and L4 radiculopathy, and elective decompression surgery was scheduled a few days later. We performed discectomies at L2/3 and L3/4 and left unilateral laminectomy at L2 and L3 for bilateral decompression. Following an uneventful surgery, the patient was extubated, and her left leg pain improved, but pain over the right outer calf with drop foot developed. A second lumbar MRI the next day revealed no evidence of recurrent disc herniation or epidural hematoma. Then, she received nerve conduction velocity and needle electromyogram on postoperative day 2, and the studies indicated right common peroneal nerve entrapment neuropathy. After medication with steroids and foot splint use, right leg pain improved. However, weak dorsiflexion of the right ankle persisted. We referred this patient to a physiatrist and OPD for follow-up after discharge. Perioperative peripheral nerve injury (PPNI) is most commonly caused by peripheral nerve ischemia due to abnormal nerve lengthening or pressure and can be exacerbated by systemic hypotension. Any diseases affecting microvasculature and anatomical differences may contribute to nerve injury or render patients more susceptible to nerve injury. Prevention, early detection and intervention are paramount to reducing PPNI and associated adverse outcomes. The use of intraoperative neuromonitoring theoretically allows the surgical team to detect and intervene in impending PPNI during surgery.